Hubungan Pendapatan Keluarga Dengan Keteraturan Pemeriksaan Anc Pada Ibu Hamil Trimester III Di Wilayah Puskesmas Kampung Delimatahun 2024 - Tamba, Febrina; Lugita , Liya; Lestari, Nimas Ayu (Utami Publisher, 2025)
In the Kampung Delima Community Health Center area, the regularity of ANC examinations among pregnant women in their third trimester has become a particular concern. Based on initial data from the Kampung Delima Health Center, there is variation in the regularity of ANC examinations that is suspected to be related to differences in family income. According to data from the Kampung Delima Health Center, the number of pregnant women who do not comply with pregnancy examinations remains relatively high. This study aims to determine whether there is a relationship between family income and the regularity of ANC examinations among pregnant women in their third trimester in the Kampung Delima Health Center area. The design of this research is a quantitative study with a cross-sectional approach. The sample size for this study consists of 43 pregnant women. Data collection was conducted using a research questionnaire. The results of the study show that the Chi-Square test analysis indicates no significant relationship between family income levels and the regularity of ANC examinations in the third trimester. The statistical test results show a Pearson Chi-Square value with a significance value of 0.516, which is greater than the significance threshold of 0.05. This means that neither the husband's nor the wife's income has a significant effect on the regularity of ANC examinations, leading to the acceptance of the null hypothesis (Ho). The researchers recommend that the health center should emphasize the importance of ANC examinations and encourage applied research to improve the regularity of examinations in the community.